FAKTOR YANG MELATARBELAKANGI PETANI KARET BEKERJA PADA DIVISI SEI LAKITAN POM PT. PP. LONDON SUMATERA INDONESIA TBK DI DESA MARGA BARU KECAMATAN MUARA LAKITAN KABUPATEN MUSIRAWAS - Fauzi, Ahmad; H. Anang, Rahidin; Abubakar, Rafeah (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2017)
ABSTRACT This research was conducted to determine the factors behind the rubber farmers working on Sei Lakitan Pom Division of PT. PP. London Sumatera Indonesia Tbk and to calculate the income contribution of rubber farmers working on Sei Lakitan Pom Division of PT. PP London Sumatera Indonesia Tbk on the income of farmer's family. This research was conducted in Marga Baru Village Muara Lakitan District Musirawas Regency. In February Up to April 2017. The research method used is survey method, for Sampling Method used by Purposive Sampling method. Data Collection Methods used Interview method directly to the respondents who have been determined by using the quisionary aids that have been prepared before and secondary data. Data processing is done using descriptive method with qualitative approach and for second problem using formula systematically. From the research results showed that the factors of income and land factors that lie behind the rubber farmers work on the Division of Sei Lakitan Pom PT. PP London Sumatera Indonesia Tbk and income contribution of rubber farmers work at Sei Lakitan Pom Division PT.PP London Sumatera Indonesia Tbk by 73 percent to family income.